Math, asked by Ritul33, 1 year ago

Verify that : x³ + y³ + z³− 3xyz =

1/2 (x + y + z)[(x − y)² + (y − z)² + (z − x)2²]​

Answers

Answered by srikanthn711
54

<body bgcolor="black"><font color="yellow">

\huge\boxed{\underline{\mathcal{\red{A} \green{N}\pink{S}\orange{W}\blue{E}\pink{R}}}}

<font color="yellow">

First We take R.H.S & use the Formula [( a-b)²= a²+b²-2ab] & simplify it then R.H.S becomes equal to L.H.S

<font color="silver">

R.H.S

⇒ 1/2×(x + y + z) (x²+ y²-2xy +y²+ z²-2yz+x²+z²-2xz)

[( a-b)²= a²+b²-2ab]

<font color="cyan">

⇒ 1/2×(x + y + z) (2x²+ 2y²+2z²-2xy -2yz-2xz)

<font color="yellow">

⇒ 1/2×(x + y + z) 2(x² + y²+ z² – xy – yz – xz)

<font color="blue">

=(x + y + z) (x² + y²+ z² – xy – yz – xz)

<font color="pink">

= x³+y³+z³-3xyz

<font color="green">= L.H.S

We know that,

[x³+ y³ + z³– 3xyz = (x + y + z)(x²+ y² + z² – xy – yz – xz)]

<font color="red ">

L.H.S = R.H.S

[x³+ y³ + z³– 3xyz = (x + y + z)(x²+ y² + z² – xy – yz – xz)]

<font color="cyan">

Hope this will help you..

{\bf{\orange{FOLLOW ME}}}

Answered by Anonymous
19

Answer:

First We take R.H.S & use the Formula [( a-b)²= a²+b²-2ab] & simplify it then R.H.S becomes equal to L.H.S

R.H.S

⇒ 1/2×(x + y + z) (x²+ y²-2xy +y²+ z²-2yz+x²+z²-2xz)

[( a-b)²= a²+b²-2ab]

⇒ 1/2×(x + y + z) (2x²+ 2y²+2z²-2xy -2yz-2xz)

⇒ 1/2×(x + y + z) 2(x² + y²+ z² – xy – yz – xz)

=(x + y + z) (x² + y²+ z² – xy – yz – xz)

= x³+y³+z³-3xyz

 = L.H.S

We know that,

[x³+ y³ + z³– 3xyz = (x + y + z)(x²+ y² + z² – xy – yz – xz)]

L.H.S = R.H.S

[x³+ y³ + z³– 3xyz = (x + y + z)(x²+ y² + z² – xy – yz – xz)]

Similar questions